Kinosao Sipi Minisowin Agency: Creating a Community Response for Special Needs Children - Ducharme, Charlene; Muskego, Doreen; Muswagon, Alfred; Paupanekis, Clarence; Muswagon, Mike; Spence, Walter; Ramdatt, Jacqueline (First Peoples Child & Family Review, 2007)
The Children’s Special Services program was created by the Kinosao Sipi Minisowin Agency to meet the requirements of special needs children and their families in the Norway House Cree Nation community of Manitoba. While the program itself is an excellent resource, its creation highlights the challenges faced by Aboriginal children with special needs and their families in regards to accessing services. Speciﬁcally, the creation of the program draws attention to the service vacuum that Aboriginal children with special needs must face. The value of the program to thecommunity cannot be underestimated as due to its existence, fewer parents have to make the choice of either placing their children in foster care or moving from their community in order to access services.